Synthesis and Characterization of New Derivatives of 1,3-Oxazepine via Cycloaddition Reactions [2+5] of Selected Carboxylic Acid Anhydrides with Azomethines Derived from 4,4'-Methylenebis(3-chloroaniline) - Ahmed Khames Ramadan (Journal of Global Pharma Technology, 2018)
Number of new derivatives of 1,3-oxazepinewere synthesized by cycloaddition reaction (2+5) of (NE,N'E)-4,4'-methylenebis (3-chloro-N-(4-halobenzylidene)aniline) with exo-3,6-epoxy-1,2,3,6-tetrahydrophthallic anhydride, tetrachlorophthalic anhydride and citraconic anhydride by refluxing in dry benzene. (NE, N'E)-4,4'-Methylenebis(3-chloro-N-(4-halobenzylidene)anilines)were prepared by thermal condensation of 4,4'-Methylenebis(3-chloroaniline) and p-halobenzaldehydes in absolute ethanol under reflux conditions. The structure of the target compounds were characterized by their spectral data of FT-IR and 1H-NMR.Keywords: Azomethines, Carboxylic Acid Anhydrides, 1, 3-Oxazepine.